Temporal Variation of Water Yield from a Treated Hilly Watershed in Lower Himalayas - Tiwari, A. K.; Bhatt, V. K.; Bansal, R. C. (Indian Forester, 2012)
The Shivalik range of Himalayas, represent the most fragile ecosystem in India. In order to restore the ecological environment in this area, a hilly watershed typical of the region of 21 ha area was brought under study in 1963. The watershed has been under complete protection and was treated by soil and water conservation measures during 1963-64. A dam of height 5.5 m was constructed across the main channel to store 0.54 ha-m of water at the strategic location. Low cost check dams and water spreaders to dissipate the erosive force of runoff and arresting sediment were constructed mainly in the first and second order streams. Temporal changes in water yield from hilly catchment of Shivalik were monitored for forty years (1963-2003). Initially the results have been highly encouraging as due to protection and management there was drastic reduction in water yield. However, the trend changed after sometime questioning the sustainability of soil and water conservation treatment in the watershed and the change in vegetation composition.